Dihydroarteannuin Ameliorates Collagen-Induced Arthritis Via Inhibiting B Cell Activation by Activating the FcγRIIb/Lyn/SHP-1 Pathway - Hu, Congqi; Wu, Danbin; Yu, Jiahui; Xu, Jia; Liu, Lijuan; Zhang, Mingying; Jiao, Wei; Chen, Guangxing (Frontiers in Pharmacology, 2022)
Background: Dihydroarteannuin (DHA), which is extracted from the traditional Chinese herb Artemisia annua L, exhibits potent immunosuppressive activity in rheumatoid arthritis (RA). Strong evidence indicates that B cells act as an essential factor in the pathogenesis of RA, but research on the immunosuppressive function of DHA in regulating B cells is limited. Objective: To investigate the modulatory effects of DHA on joint destruction, proinflammatory cytokine production, proliferation, apoptosis and activation of B cells and to explore the possible associated mechanism in RA treatment. Methods: Mice were allocated into four groups: control group (untreated), model group (arthritis-induced), DHA group (arthritis + DHA), methotrexate (MTX) group (arthritis + MTX). Weight and joint oedema were record weekly, and joint damage was detected by micro-CT scan. Burkitt’s lymphoma ST486 human B cells lacking endogenous Fc gamma receptor b (FcγRIIb) were transfected with a 232Thr loss-of-function mutant to construct FcγRIIb-mutant cell lines (ST486) for in vitro experiments. The mRNA and protein levels of proinflammatory cytokines produced by ST486 cells were measured by quantitative real-time PCR and ELISA. The proliferation of ST486 cells was assessed with Cell Counting Kit-8. Apoptosis and activation were tested by flow cytometry. The effects of DHA on the activation of FcγRIIb, protein tyrosine kinases (Lyn), and Src homology 2 (SH2)-containing tyrosine phosphatase-1 (SHP-1) signaling pathways were determined by western blotting. Results: In comparison to model group, bone mineral density (BMD) and bone volume/tissue volume (BV/TV) were increased, whereas joint oedema was decreased in both of the DHA and MTX group. Interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) mRNA and protein levels were decreased after treatment with DHA. In addition, DHA treatment inhibited the proliferation and activation and promoted the apoptosis of ST486 cells in vitro. Furthermore, the protein levels of FcγRIIb, Lyn, and SHP-1 were all increased after DHA treatment. Moreover, the induced expression of phosphorylated CD19 was also inhibited by DHA. Conclusion: We provide the first evidence that DHA may alleviate collagen-induced arthritis in part by activating the FcγRIIb/Lyn/SHP-1 pathway in B cell, indicating that DHA is a novel and valuable candidate for RA therapy.